E-Payment Gateway Service in Malaysia and the Analysis of its Legal Framework - Zulhuda, Sonny (INSI Publications, 2012)
Electronic payment has emerged in the past decade as an alternative of payment system between business-to-business as well as when involving individuals. Electronic payment is made much easier and affordable today by the emergence of products and services offered by various parties including financial institutions and web-based online portals. There is a need to relook at the provision of legal basis for such services and products in order to ensure all the interests of the users (in both ends) are legally and effectively protected. This paper looks at the legal framework of e-payment gateway services in Malaysia, in particular on the primary legislation on e-payment services in the form of the Payment Services Act 2003.